The Relationship Between Total IgE, Symptom Duration, VAS Scores, and Danyoung Classification in Allergic Rhinitis - Ayunita Tri Wirattami; Tanti Agustina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Allergic Rhinitis (AR) is an inflammatory condition of the nasal mucosa triggered by allergies, with total IgE often used as a biomarker to assess disease severity. Objective: To analyze the relationship between total IgE levels, symptom duration, Visual Analog Scale (VAS) scores, and Danyoung Classification in AR patients. Methods: A cross-sectional observational analytical study was conducted on 73 patients at the Allergy-Immunology Clinic of Dr. Saiful Anwar General Hospital. Total IgE levels were measured using the ELISA method, while VAS and nasal mucosa classification were assessed through anamnesis and nasoendoscopy. Results: The study showed68.5% of patients had IgE levels above 100 IU/ml, with an average of 982.97 IU/ml. Although higher IgE levels were often found in AR patients, there was no statistically significant correlation between IgE levels and Danyoung classification (significance value 0.924). The correlation test showed a coefficient of -0.11, indicating a negative correlation, but it was not statistically significant. Conclusion: The nasal mucosa condition in patients with high IgE levels does not always reflect severe inflammation. In addition to IgE levels, external factors such as exposure to pollutants and cigarette smoke also play a role in the condition of the nasal mucosa. Therefore, while high IgE levels often indicate allergic reactions, this study found no significant relationship between IgE levels and AR severity.